Photochemical Synthesis of Gold Nanoparticles by Irradiation of Gold Chloride with the 2nd Harmonic of a Nd:YAG Laser - Barbosa,Henrique F. P. (2019)
A synthesis method was developed capable of obtaining pristine gold nanoparticles (AuNPs) using the lowest possible amount of auxiliary compounds. An aqueous solution of HAuCl4.3H2O was irradiated, in the absence of any stabilizing species, with the 532-nm radiation of a Nd:YAG laser. Spherical shaped AuNPs were produced by this method with sizes below 10 nm. The crystalline structures were stable for up to 28 days. A mechanism for this process is also proposed based on the initial cleavage of water molecules by the laser irradiation followed by the formation of hydrogen peroxide that reduces the gold species AuIII. The resulting species of these reactions (H2 and O2) were identified by mass spectrometry. This new method suggests that laser irradiation is a feasible alternative to produce ready-to-use AuNPs, for drug delivery, diagnostics or bio-imaging.